The Effectiveness of Using STEM (Science, Technology, Engineering, Mathematics) Approach-Based LKPD on the Science Process Skills of Grade X Students in Bacteria Material - Iwan Ridwan Yusup Iwan; Akni Jinatun Nurutami; Ukit Ukit (CV. Generasi Intelektual Digital (GEN ID), 2026)
The teaching materials on bacteria presented at the senior high school level are still abstract and require scientific activities, but there are not many student worksheets that guide students in developing scientific process skills as one of the 21st century skills. This study aims to determine the effectiveness of using STEM (Science, Technology, Engineering, Mathematics) approach-based worksheets in improving the scientific process skills of grade X students on the subject of bacteria. The research was conducted at SMAN 26 Bandung using a quantitative method with a non-equivalent control group quasi-experimental design. Data were collected through pre-tests and post-tests and analysed using normality tests, homogeneity tests, N-Gain tests, and independent sample t-tests. The results showed that the N-Gain score for the experimental class was 0.6041 (moderate category), higher than that of the control class, which was 0.0435 (low category). The average post-test score of the experimental class (79.52) was also higher than that of the control class (76.26). The conclusion of the study shows that STEM-based worksheets are very suitable as a learning medium and have a significant effect on improving students' science process skills in the subject of bacteria.